Serum ferritin and red blood cell indices in infants of diabetic mothers (BIRDEM Medical Journal, 2020)
Background: Fetal iron stores are affected by maternal diabetes and it is lower at birth in infants of diabetic mothers (IDMs). Risks for developing iron deficiency and neurocognitive impairment are reported in IDMs. This study was done to assess serum ferritin and red cell indices in IDMs and to compare the values with infants born to mothers without diabetes mellitus.Methods: This cross-sectional study was carried out at BIRDEM General Hospital from March to October, 2018. Total 102 full term neonates were included in this study. Among them 70 neonates were IDMs and 32 were infants born to mother without diabetes mellitus. Serum ferritin and red cell indices like hemoglobin (Hb), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW) were measured within 48 hours of birth. Comparison of red cell indices and serum ferritin level were done between IDMs and infants of non-diabetes mothers. Statistical analysis was performed by using Epi info, and p value of